Characterization of Arabidopsis thaliana CPR5 via the elucidation of interacting protein partners : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Biochemistry at Massey University, Palmerston North, New Zealand - Chiem, Fiona (Shane) (Massey University, 2015)
he Arabidopsis thaliana Constitutive expresser of pathogenesis related genes5 (CPR5) has previously been suggested to play a role in the regulation of disease resistance, plant and cell proliferation, development and death. Analysis of cpr5 mutant alterations to hormone and hormone-like signalling mechanisms have provided evidence that abolishment of CPR5 involvement within these hormone signalling pathways, results in many of the stunted growth, early senescence and constitutive expression of pathogen defense phenotypes observed. Despite the pleiotropic effect that cpr5 mutants have on the plant system, it is unclear whether CPR5-dependent pathways are due to a direct interaction with CPR5 or due to a more indirect association. CPR5 has been proposed to be a regulator of a multitude of different pathways, including reactive oxygen species (ROS), cell wall biosynthesis, and transcription but evidence of these proposals are limited to the effects that cpr5 mutants have on downstream targets. In an attempt to address the involvement of CPR5 in Arabidopsis plant processes, a series of studies were conducted to determine the protein interacting partners of CPR5. Proteins were identified via 2 independent yeast 2 hybrid (Y2H) screening of an Arabidopsis transcriptome library. Ten proteins of interest were identified via two independent screenings using two truncated forms of CPR5. Functional involvement of CPR5 with the identified proteins was further explored using the Y2H pairwise interaction system. CPR5 was found to interact with 3 full length proteins identified. To explore the possibility that CPR5 interacts with multiple protein partners in different locations within the cell, Bifluorescence molecular complementation assays were performed to determine the localization and interaction of CPR5 with the ten identified genes as well as 3 previously identified genes. Several novel interactions were identified that occur within the nucleus and outside of the nucleus. Not only was CPR5 confirmed to have an interaction with KRP2 within the nucleus, CPR5 exhibited interaction with FSD1, CRK4, PATL3, PATL5, and PATL6, outside of the nucleus. In the final set of experiments, several double mutant lines were produced that did not yield any observable phenotypes that differ from cpr5-2 single mutant plants. In order to determine the effects these double mutants have on various plant processes affected by cpr5-2 single mutant; qRT-PCR was performed to determine the expression pattern of pathogen related genes (PR1 and PDF1.2) known to be significantly upregulated in cpr5-2 plants. qRT-PCR analysis revealed that cpr5-2 fsd1 exhibits a down-regulation of PDF1.2. PR1 regulation was found to be down-regulation in cpr5-2 bzip61 and up-regulated in cpr5-2 patl3 compared to cpr5-2. Sugar and dark treatment of the cpr5-2 double mutant lines yielded several alterations to hypocotyl length, root length, and apical hook curvature by several of the double mutant lines, indicating a connection between CPR5 and the knocked out gene of interest. None of the double mutants were able to completely rescue the sugar-induced morphological phenotypes exhibited by cpr5-2, and some double mutant lines exhibited more pronounced effects indicating an additive effect by sugar treatment. Together this data suggests that CPR5 interacts with various proteins involved in different plant processes in various locations throughout the cell. Further research of these proteins and a more direct analysis of the interaction that may occur between CPR5 and these proteins will be required to provide a foundation for more direct characterization the CPR5 molecular function; and ultimately to determine the role that CPR5 plays within the hormone and hormone like signalling pathway and their effects on major plant processes.